Observation of the cosmic ray shadow of the Sun with the ANTARES neutrino telescope. (24th September 2021) - Romanov, A.; Sanguineti, M.
Abstract: ANTARES is the largest undersea neutrino telescope and it has been taking data in its final configuration for more than ten years. On their journey to the Earth, cosmic rays can be absorbed by celestial objects, like the Sun, leading to a deficit in the atmospheric muon flux measured by the ANTARES detector, the so-called Sun "shadow" effect. This phenomenon can be used to evaluate fundamental telescope characteristics: the detector angular resolution and pointing accuracy. This work describes the study of the Sun "shadow" effect using the ANTARES data collected between 2008 and 2017. The statistical significance of the Sun shadow observation is 3.7σ and the estimated angular resolution value of the ANTARES telescope for downward-going muons is 0.59°±0.10°, which is consistent with the expectations obtained from the Monte Carlo simulations and also with the estimation from the Moon "shadow" analysis of 2007-2016 years. No evidence of systematic pointing shift is found and the resulting pointing accuracy is consistent with the expectations.